Magnetic resonance imaging of placentome development in the pregnant Ewe. (February 2021) - Flouri, Dimitra; Darby, Jack R.T.; Holman, Stacey L.; Perumal, Sunthara R.; David, Anna L.; Morrison, Janna L.; Melbourne, Andrew
Abstract: Introduction: Novel imaging measurements of placental development are difficult to validate due to the invasive nature of gold-standard procedures. Animal studies have been important in validation of magnetic resonance imaging (MRI) measurements in invasive preclinical studies, as they allow for controlled experiments and analysis of multiple time-points during pregnancy. This study characterises the longitudinal diffusion and perfusion properties of sheep placentomes using MRI, measurements that are required for future validation studies. Methods: Pregnant ewes were anaesthetised for a MRI session on a 3T scanner. Placental MRI was used to classify placentomes morphologically into three types based on their shape and size at two gestational ages. To validate classification accuracy, placentome type derived from MRI data were compared with placentome categorisation results after delivery. Diffusion-Weighted MRI and T2-relaxometry were used to measure a broad range of biophysical properties of the placentomes. Results: MRI morphological classification results showed consistent gestational age changes in placentome shape, as supported by post-delivery gold standard data. The mean apparent diffusion coefficient was significantly higher at 110 days gestation than at late gestation ( 140 days; term, 150 days). Mean T2 was higher at mid gestation (152.2 ± 58.1 ms) compared to late gestation (127.8 ms ± 52.0). Significantly higher perfusion fraction was measured in late gestation placentomes that also had a significantly higher fractional anisotropy when compared to the earlier gestational age. Discussion: We report baseline measurements of techniques common in placental MRI for the sheep placenta. These measurements are essential to support future validation measurements of placental MRI techniques. Highlights: Describe baseline MRI characteristics of sheep placenta. Placentome perfusion and fractional anisotropy increases with increasing gestation. Placentome T2 falls with increasing gestation. Placentome ADC and T2 change between type A and type B placentomes. Fractional anisotropy remains similar between different placentome types.